Oral mite anaphylaxis: who, when, and how?. Issue 3 (June 2020) - Sánchez-Borges, Mario; Capriles-Hulett, Arnaldo; Fernandez-Caldas, Enrique
Abstract : Purpose of review: To present an update on the recent advances in the understanding of the mechanisms and practical management of oral mite anaphylaxis (OMA, pancake syndrome). Recent findings: Among novel observations regarding OMA, this review highlights the increased prevalence of aspirin/NSAID hypersensitivity inpatients affected by OMA, the association of OMA with exercise-induced anaphylaxis, the presentation of OMA simulating acute asthma, the occurrence of OMA in childhood, the high severity and lethal potential of OMA, the contamination of other foods, such as oat and corn flour with mites, and the simultaneous induction of OMA symptoms in more than one individual exposed to the same food source. Summary: OMA is a severe, potentially lethal, acute allergic condition that should be suspected whenever symptoms begin soon after the intake of mite-contaminated foods. Physician awareness on this clinical picture is of paramount importance to establish a correct diagnosis and to implement adequate preventive measures to help patients at risk to avoid its occurrence.